2019
DOI: 10.1071/an17741
|View full text |Cite
|
Sign up to set email alerts
|

Addition of several tannin extracts to modulate fermentation of barley meal under intensive ruminant feeding conditions simulated in vitro by incubating at pH 6.0–6.2

Abstract: The potential use of tannin extracts from quebracho (QCT), grape (GCT), chestnut (CHT) and oak (OHT) included at 10, 20 or 30 mg/g to modulate rumen fermentation of concentrates was studied in three 24-h in vitro incubation runs, with barley grain as reference substrate and simulating high concentrate feeding conditions by adjusting pH at 6.2. Incubation pH at 8 and 24 h ranged from 6.14 to 6.18 and from 5.94 to 6.00, respectively. Gas production from barley alone (CTL) was linearly reduced with CHT (P &lt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Regarding gas production after 24 h of fermentation, the results in the literature are quite variable. Some have reported reduced gas production [ 29 , 43 ], some were unchanged [ 27 ], while Wei et al [ 24 ] reported increased gas production. In the present study, the addition of 0.2% and 0.3% PICB did not significantly increase gas production when compared with the control group, even though the experimental values were marginally higher.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding gas production after 24 h of fermentation, the results in the literature are quite variable. Some have reported reduced gas production [ 29 , 43 ], some were unchanged [ 27 ], while Wei et al [ 24 ] reported increased gas production. In the present study, the addition of 0.2% and 0.3% PICB did not significantly increase gas production when compared with the control group, even though the experimental values were marginally higher.…”
Section: Discussionmentioning
confidence: 99%